Examining the functional range of commercially available low‐cost airborne particle sensors and consequences for monitoring of indoor air quality in residences. (10th December 2019) - Zou, Yangyang; Young, Matthew; Chen, Jiawei; Liu, Jiaqi; May, Andrew; Clark, Jordan D.
Abstract: Low‐cost airborne particle sensors are gaining attention for monitoring human exposure to indoor particulate matter. This study aimed to establish the concentrations at which these commercially available sensors can be expected to report accurate concentrations. We exposed five types of commercial integrated devices and three types of "bare" low‐cost particle sensors to a range of concentrations generated by three different sources. We propose definitions of upper and lower bounds of functional range based on the relationship between a given sensor's output and that of a reference instrument during a laboratory experiment. Experiments show that the lower bound can range from approximately 3 to 15 μg/m 3 . At greater concentrations, sensor output deviates from linearity at approximately 300‐3000 μg/m 3 . We also conducted a simulation campaign to analyze the effect of this limitation on functional range on the accuracy of exposure readings given by these devices. We estimate that the upper bound results in minimal inaccuracy in exposure quantification, and the lower bound can result in as much as a 50% error in approximately 10% of US homes.